Bakery-liscious - Ishak, Nur ‘Ibrah; Manap, Nurul Aini; Ahmad Mukhlis, Nurul Nazirah; Mohd Noor, Massarah (2021)
Bakery-Liscious is a business that provides a wide variety of breads without preservatives. This Bakery-Liscious business sells a unique product and is different from other products where it produces breads with high quality ingredient and it produces bread that does not use any preservatives such as calcium propionate and potassium bromate into bread and added a secret ingredient in the bread. Bakery-Liscious is a new business that based in Johor. This location is a strategic place because it can attract locals in the nearby area, especially employees because they will be the dominant target market to come and buy bread at our store. The business plan for this Bakery-Liscious is to provide various information related to the business to be conducted and it also involves research on the competition and the size of the market to be faced where it allows us to provide the best business plan to make this Bakery-Liscious business running smoothly and to face existing competitors in the market. In addition, the mission of Bakery-Liscious is to ensure that customers who come to our store, will be satisfied with the quality of bread without preservatives which is can enjoy the nutritious bread that use high quality product and the excellent service provided. This Bakery-Liscious is a business partnership that consists of 4 partners and these four partners have their own skills that can help them to promote their products to customers and manage the business using the knowledge and skills they have. This business is operated by 5 managers as head of department and one of the managers, we hired him to be the manager and has 2 bakers and 2 general works. The 5 managers will play their own role as general manager, administration manager, marketing manager, operation manager and financial manager. With this administration, marketing and operations plan, it can ensure that the bread without preservative products that will be produced can satisfy customers who buy and then can expand this Bakery-Liscious business throughout the state after doing some analysis in terms of financial plan and others aspect, this business has shown an increase in bread sales every year. We also hope that our business Bakery-Liscious will become the best bakery business in Malaysia.